2022
DOI: 10.1140/epjqt/s40507-022-00122-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing robustness of noisy qutrit teleportation with Markovian memory

Abstract: Quantum teleportation is the fundamental communication unit in quantum communication. Here, a three-level system is selected for storing and transmitting quantum information, due to its unique advantages, such as lower cost than a higher-level system and higher capacity and security than a two-level system. It is known that the key procedure for perfect teleportation is the distribution of entanglement through quantum channel. However, amounts of noise existing in the quantum channel may interfere the entangle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…The effect of a depolarizing channel on a state is to incoherently mix the state with white noise with a nonzero probability. The effect of this channel on various quantum communication protocols, for example, (1) on quantum teleportation 45 , (2) for a qutrit 46 , (3) on the key rate and hence, on security of quantum key distribution protocol 50 , and, (4) on quantum secret sharing protocol 51 have been studied.…”
Section: Information Transfer With Qu N Itsmentioning
confidence: 99%
“…The effect of a depolarizing channel on a state is to incoherently mix the state with white noise with a nonzero probability. The effect of this channel on various quantum communication protocols, for example, (1) on quantum teleportation 45 , (2) for a qutrit 46 , (3) on the key rate and hence, on security of quantum key distribution protocol 50 , and, (4) on quantum secret sharing protocol 51 have been studied.…”
Section: Information Transfer With Qu N Itsmentioning
confidence: 99%
“…Quantum communication, an indispensable branch of quantum information, mainly involves quantum teleportation [1][2][3][4][5], quantum dense coding [6][7][8], quantum secret sharing [9][10][11] and quantum key distribution [12][13][14]. Quantum communication, leveraging the intrinsic characteristics of quantum mechanics, offers a significantly higher level of security than classical communication [15].…”
Section: Introductionmentioning
confidence: 99%
“…The study optimised the teleportation technique for noisy quantum channels using generalised quantum measurement frameworks. Xu et al [36] developed a memory channel model during the entanglement distribution phase and obtained a uniform equation for the evolution of a two-qutrit entangled state under various types of correlated noise. They demonstrated that three-level teleportation using Pauli and amplitude-damping channels can generally enhance noise robustness if the quantum channel's Markovian correlations are considered.…”
Section: Introductionmentioning
confidence: 99%